1994
DOI: 10.1021/ac00077a009
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Retention Index Concept in Micellar Electrokinetic Capillary Chromatography

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 26 publications
7
77
1
Order By: Relevance
“…Based on the criteria for reference compounds in LC, suggested by Smith [ 18] and Pac~ikovfi and Feltl [4[, the following requirements were formulated for a homologous series to be applicable as retention index scale in MEKC [12]: 1. relationship between log k and the number of carbon atoms in the homologues must be linear; 2. lowest homologue should be reasonably polar, in order to obtain a wide scale of retention indices, covering the greater part of the elution window; 3. should contain a strong chromophore to detect them spectrophotometrically, as most CE instruments apply on-column UV detection; 4. should not possess an electrophoretic mobility,…”
Section: Homologous Seriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the criteria for reference compounds in LC, suggested by Smith [ 18] and Pac~ikovfi and Feltl [4[, the following requirements were formulated for a homologous series to be applicable as retention index scale in MEKC [12]: 1. relationship between log k and the number of carbon atoms in the homologues must be linear; 2. lowest homologue should be reasonably polar, in order to obtain a wide scale of retention indices, covering the greater part of the elution window; 3. should contain a strong chromophore to detect them spectrophotometrically, as most CE instruments apply on-column UV detection; 4. should not possess an electrophoretic mobility,…”
Section: Homologous Seriesmentioning
confidence: 99%
“…Muijselaar et al [12] applied n-alkylbenzenes and alkylaryl ketones as retention index standards in sodium dodecyl sulphate (SDS), cetyltrimethylammonium bromide (CTAB) and dodecyltrimethylammonium bromide (DTAB) surfactant systems. In Fig.…”
Section: Homologous Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…LSER studies are also based on a thermodynamic approach and provide quantitative information about different solute-micelle interaction phenomena. They can be used to elucidate which mechanisms play a dominant role in Presented at the 21 st ISC held in Stuttgart, Germany, 15th-20 th September, 1996 Previously we demonstrated that the retention index, I, is a good migration parameter to compare different surfactant systems since I is independent of the concentration, molar volume and critical micelle concentration of the applied surfactant [8]. For a given sample compound in a specific surfactant system, SF, a AIsF value can be calculated according to:…”
Section: Evaluation and Characterization Of Pseudo-stationary Phases mentioning
confidence: 99%
“…Several research groups [7][8][9][10][11][12][13][14] 2 which tabulated the data as log P x,SDS/water values. In several recent studies researchers expressed the solute concentrations in molarity and reported either the molarity-based partition coefficient, P c,SDS/water , or a binding constant K s .…”
Section: Introductionmentioning
confidence: 99%